1990
DOI: 10.1111/j.1528-1157.1990.tb05490.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Study of the GAB A‐Withdrawal Syndrome in Rats

Abstract: The spatial and temporal EEG features of the epileptogenic syndrome induced by cessation of chronic intracortical GABA infusion in normal rats are described. In the initial stages, the paroxysmal discharges (PDs) induced by withdrawal from unilateral GABA application may appear either unilaterally or bilaterally, although with greater amplitude on the infused side. PDs are transitorily accompanied by behavioral signs of distal myoclonus of the body territory corresponding to the infused area (contralateral hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is worth noting that after washing out muscimol from the epidural cup, withdrawal‐seizures such as those described by Brailowsky et al. (1990) following long‐term cortical GABA infusions, were not observed in any of the described experiments.…”
Section: Resultsmentioning
confidence: 59%
“…It is worth noting that after washing out muscimol from the epidural cup, withdrawal‐seizures such as those described by Brailowsky et al. (1990) following long‐term cortical GABA infusions, were not observed in any of the described experiments.…”
Section: Resultsmentioning
confidence: 59%
“…However, it is not clear how silencing of the network would downscale synaptic weights and firing rates. According to the homeostatic scaling model (Turrigiano and Nelson, 2004), prolonged silencing of neurons leads to a rebound elevation of spiking (Brailowsky et al 1990). Prolonged network silencing after cortical deafferentation was suggested to be the cause of trauma-induced epileptic excitability (Avramescu and Timofeev, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The model thus differs from those focal epilepsy models in which focal epileptiform activity does not become generalized. For example, in the g-aminobutyric acid (GABA)withdrawal focal epilepsy model 35 the epileptogenic process somehow remains localized and limited to the original focus. Our results further showed that, unlike several other generalized cortical seizure models, 36 in the iron-epilepsy model the spike-wave epileptiform activity of the cortical focus is propagated in to the limbic structures.…”
Section: Discussionmentioning
confidence: 99%